Semi-Automatic Chapati Roller Machine - ROSLI, MUHAMMAD EMIR DANIAL; DEWI @ MOHD SOFFIAN, ASHRAFFI ADLI; OTHMAN, KHAIRULNIZAM (Multidisciplinary Applied Research and Innovation, 2022)
Semi-automatic Chapati Roller Machine is the machine that give a solution for user to press the dough to be exact chapati thickness in a short time. Other machines in market are industrial types which is heavy, complex, and high cost. This research is aim for smaller industrial or home-based business which is who just started into this industry to have a machine that make their production faster and bigger with low-cost modal and maintenance. Along with the development of small industrial market, these two classes either high or mid-class, the field on running the Chapati’s market has already been high demand. The Chapati Roller machine must be long lasting product and can mass produce chapati in the short time. In Malaysia, this 4machine is not popular than in India because the small businesses still use old traditional method. The problem is the supply cannot overtake the demands. Many small businesses in Chapati making are still using traditional method such as using rolling pins. They just can make 200 to 400 pcs of chapatis per day. This phase cannot keep its demand. So, the solution is to build a low cost semi-automatic Chapati roller machine. We study materials to realize why they carry on the way they do so we may utilize that information to settle on great designing choices in picking the correct materials for the work thus that we may, if important, search out techniques for making materials that will serve our requirements best.